The taboo of retreat: The politics of sea level rise, managed retreat, and coastal property values in California. Issue 2 (14th February 2022) - Anderson, Ryan B.
Abstract : This article uses anthropological and historical perspectives to explore ongoing conflicts over "managed retreat" and property values along the California coast. Proponents of managed retreat argue that coastal communities need to start planning for the impending effects of sea level rise, including retreating or relocating away from vulnerable coastal spaces. Some residents and organizations oppose such measures, often citing the need to protect coastal home and real estate values. One of the key arguments of some residents is that such coastal properties should be protected because they are so valuable. Drawing from sociological and anthropological theories of value, in addition to ethnographic research in California, this article explores how this situation in California came to be, what it can tell us about the politics of value and financialization, and finally, what it portends for the future as our highly financialized world faces the looming threat of climate change.